The Algorithmic Heart: How Wearable Devices Use AI for Proactive Health Monitoring - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The convergence of wearable technology and Artificial Intelligence AI is fundamentally reshaping the landscape of digital health. Moving beyond simple data c...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics